2014
DOI: 10.4103/0253-7613.129326
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-induced palmoplantar erythrodysesthesia syndrome and long-lasting multiple nail changes

Abstract: Palmoplantar erythrodysesthesia syndrome (PPES) and nail changes are common presentations of cutaneous toxicity of docetaxel chemotherapy, which deteriorate the quality of life of patients. Herein, we describe a female patient who developed PPES and multiple nail changes due to docetaxel treatment for infiltrative ductal carcinoma. Cold application and elevation of extremities during docetaxel infusion, potent topical steroids and oral pyridoxine increased the tolerance to chemotherapy and provided regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…The rapid expansion of novel anticancer agents has resulted in significant advances in the treatment of cancer patients but has also broadened the spectrum of cutaneous adverse events. Conventional chemotherapeutic agents are well known to cause cutaneous reactions including hand‐foot syndrome (palmoplantar erythrodysesthesia), neutrophilic eccrine hidradenitis, radiation recall dermatitis, alopecia, hyperpigmentation, urticarial hypersensitivity reaction and sclerotic reactions among many others. Although the classic cutaneous reactions associated with chemotherapy agents are well known, the histopathologic characteristics of reactions caused by the many novel anticancer agents are under‐recognized.…”
mentioning
confidence: 99%
“…The rapid expansion of novel anticancer agents has resulted in significant advances in the treatment of cancer patients but has also broadened the spectrum of cutaneous adverse events. Conventional chemotherapeutic agents are well known to cause cutaneous reactions including hand‐foot syndrome (palmoplantar erythrodysesthesia), neutrophilic eccrine hidradenitis, radiation recall dermatitis, alopecia, hyperpigmentation, urticarial hypersensitivity reaction and sclerotic reactions among many others. Although the classic cutaneous reactions associated with chemotherapy agents are well known, the histopathologic characteristics of reactions caused by the many novel anticancer agents are under‐recognized.…”
mentioning
confidence: 99%
“…Nos 29 estudos identificados nesta revisão sistemática, n=26 (90%) apresentaram alternativas de tratamento e/ou prevenção, tanto farmacológico como não farmacológico, para pacientes acometidos com a síndrome mãopé [15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32] . A maioria dos manejos para tratamento da síndrome mão-pé publicados foi de relatos de casos.…”
Section: Discussionunclassified
“…A síndrome mão-pé é uma reação adversa muito comum durante o tratamento com agentes quimioterápicos e é um fator preditor de morbidade e mortalidade, uma vez que as lesões são portas de entrada para instalação de microrganismos e, dessa forma, implica em risco de sepse [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] .…”
Section: Discussionunclassified
“…The onset of onychopathy induced by DTX reflects dose-dependent cumulative toxicity [ 7 ] and the accumulation rate also represents an important factor predicting the severity of this adverse event. Previous studies have shown wide variation in the time of onset of onychopathy; this has therefore been difficult to predict and tended to be overlooked, resulting in late diagnosis at a severe stage, and treatment by dosage reduction or discontinuation [ 8 ]. Minisini [ 4 ] and Takeshita et al [ 9 ] reported that DTX-associated onychopathy was present at earlier time-points than those reported by clinical trials and emphasized that early treatment was important.…”
Section: Discussionmentioning
confidence: 99%